Long-term Maintenance of CD4 T Cell Memory Responses to Malaria Antigens in Malian Children Coinfected with Schistosoma haematobium - Lyke, Kirsten E.; Dabo, Abdoulaye; Arama, Charles; Diarra, Issa; Plowe, Christopher V.; Doumbo, Ogobara K.; Sztein, Marcelo B. (Frontiers in Immunology, 2018)
Polyparasitism is common in the developing world. We have previously demonstrated that schistosomiasis-positive (SP) Malian children, aged 4-8 years, are protected from malaria compared to matched schistosomiasis-negative (SN) children. The effect of concomitant schistosomiasis upon acquisition of T cell memory is unknown. We examined antigen-specific T cell frequencies in 48 Malian children aged 4-14 to a pool of malaria blood-stage antigens, Apical Membrane Antigen 1 (AMA-1) and Merozoite Surface Protein 1 (MSP-1) and to a pool of schistosomal antigens, Soluble Worm Antigenic Preparation (SWAP) and Schistosoma Egg Antigen (SEA) at a time point during a malaria episode and at a convalescent time point 6 months later, following cessation of malaria transmission. cessation 6 months later. CD4+ T cell-derived memory responses, defined as one or more significant cytokine (IFN-g, TNF-α, IL-2 and/or IL-17A) production responses, was measured to schistoma antigens in 18/23 SP children at one or both time points, compared to 4/23 SN children (P < 0.0001). At the time of malaria infection, 12/24 SN children and 15/23 SP children (P = 0.29) stimulated with malaria antigens demonstrated memory recall as defined by CD4-derived cytokine production. This compares to 7/23 SN children and 16/23 SP children (P = 0.009) at thea convalescent timepoint six months later. 46.2% of cytokine-producing CD4+ T cells expressed a single cytokine after stimulation with malaria antigen during the malaria episode. This fell to 40.9% at follow-up with a compensatory rise of multifunctional cytokine secretion over time, a phenomenon consistent with memory maturation. The majority (53.2%-59.5%) of responses derived from CD45RA-CD62L- effector memory T cells with little variation in the phenotype depending upon the time point or the study cohort. We conclude that detectable T cell memory responses can be measured against both malaria and schistosoma antigens and that the presence of S. haematobium may be associated with enhanced long-term maintenance of T memory to malaria.cell induction.